Effects of lifestyle modification and metformin on irisin and FGF21 among HIV‐infected subjects with the metabolic syndrome. (8th October 2014) - Srinivasa, Suman; Wong, Kimberly; Fitch, Kathleen V.; Wei, Jeffrey; Petrow, Eva; Cypess, Aaron M.; Torriani, Martin; Grinspoon, Steven K.
Summary Objective Few studies have investigated irisin and FGF21 to elucidate the role of these hormones to regulate 'beiging' in HIV‐infected patients. Design Fifty HIV‐infected subjects with the metabolic syndrome were previously recruited and randomized to receive lifestyle modification (LSM) and/or metformin over 12 months. In the current study, we assessed FGF21 and irisin at baseline and after intervention. In addition, we assessed circulating FGF21 and irisin in relationship to brown adipose tissue (BAT) gene expression in dorsocervical subcutaneous fat biopsies from 13 HIV‐infected subjects. Results At baseline, prior to intervention, HIV‐infected subjects demonstrated increased log FGF21 (2·13 ± 0·06 vs 1·98 ± 0·05 pg/ml, P = 0·05) and log irisin (0·33 ± 0·02 vs 0·17 ± 0·04 μg/ml, P = 0·003) compared with healthy controls well matched based on waist circumference. After 12 months, HIV‐infected subjects randomized to LSM demonstrated a relative reduction in FGF21 compared with those not randomized to LSM (−10 [−35, 22] vs 40 [0, 94] %change, P = 0·01). Changes in FGF21 were inversely associated with improved parameters of energy homoeostasis, including increased REE (ρ = −0·34, P = 0·046) and max VO2 (ρ = −0·38, P = 0·02), and reduced RQ (ρ = 0·40, P = 0·02) among all HIV‐infected subjects. Increased UCP‐1 (r = 0·75, P = 0·003), DIO2 (r = 0·58, P = 0·04) and CideA (r = 0·73, P = 0·01) gene expression in dorsocervical fat was significantly associated with FGF21 in HIV‐infected subjects. Conclusion HIV‐infected subjects with metabolic complications demonstrate increases in FGF21 in relationship to BAT gene expression. Relative reductions in FGF21 in those receiving long‐term LSM relate to overall improvements in energy expenditure parameters. In contrast, irisin levels are elevated in HIV‐infected subjects, but are not influenced by LSM nor associated with BAT gene expression.